Using The Quizizz as an Assessment of Students' English Learning - Aulia Putri Pertiwi (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
Education is becoming more advanced with increasingly sophisticated technology. The use of education-based ICT has evolved since the mid-twentieth century promoting e-learning as an alternative to facilitating student learning. The purpose of this study is to explore students' views on using the Quizizz application as an assessment tool for students' English learning. The design of this research is a qualitative approach. The sample of this research is 3 students of SMKN 1 Pakisjaya. Data was collected through observation, interviews and documentation. The results of the study showed students' perspectives on the use of Quizizz. In conclusion, the students strongly agree that the Quizizz application is a medium for learning and assessing English because this application has an attractive appearance.Keywords: Assessment, Quizizz, English Learning